Special education use in elementary school by children with nonsyndromic orofacial clefts. Issue 3 (5th December 2018) - Watkins, Stephanie E.; Allori, Alexander C.; Meyer, Robert E.; Aylsworth, Arthur S.; Marcus, Jeffrey R.; Strauss, Ronald P.
Abstract: Background: Children with nonsyndromic orofacial clefts (NS OFCs) may require exceptional children's (EC) services for academic delays. We examined EC service use of children with and without NS OFCs in NC in elementary school. Methods: We included 559 children with NS OFCs and 6, 822 children without birth defects who had NC educational records. We estimated prevalence ratios, trends in enrollment, and characteristics of eligibility classification using descriptive statistics and logistic regression by cleft subtype and race/ethnicity. We estimated the odds of third grade retention by EC enrollment using logistic regression with inverse probability of treatment weights. Results: Children with NS OFCs were 3.02 (95% CI: 2.50, 3.64) times as likely to receive third grade special education (SE) services compared to unaffected peers. The prevalence odds was highest among children with CL+P (OR: 4.61, 95% CI: 3.49, 6.09) declining by 54% by fifth grade. The prevalence odds of SE for white children was approximately 1.50 times that for African American children in fourth and fifth grades. Approximately 33% of children with NS OFCs within each racial/ethnic group received SE in third grade. African American children were twice as likely to receive services under specific learning disability. Children with NS OFCs receiving EC services were 44% (OR: 0.56; 95% CI: 0.13, 2.38) less likely to be retained in third grade compared to children with NS OFCs who were not receiving services. Conclusions: Children with NS OFCs are more likely to receive SE services in elementary school compared to their unaffected peers. The eligibility category differed by racial/ethnic group.